Antidiarrhoeal activity of rind of Punica granatum - Akter, Saleha; Sarker, Amit; Hossain, Md. Sanowar (International Current Pharmaceutical Journal, 2013)
Punica granatum (Family: Punicaceae) is a widely consumed fruit in Bangladesh locally known as Anar or Bedana. Traditionally the plant is used to treat diarrhoea, dysentery, hemorrhage, tuberculosis and chronic periodontitis. The present study was undertaken in order to justify and authenticate the traditional use of rind of P. granatum fruit in diarrhoea. Methanolic extract of the rind of the fruit was tested in castor oil- and magnesium sulfate-induced diarrhoea in mice at the doses of 200 and 400 mg/kg body weight. The results of the present study revealed significant antidiarrhoeal activity (p<0.001) in both animal models. The extract inhibited 31.25% defaecation at the dose of 200 mg/kg and 53.75% at the dose of 400 mg/kg in castor oil-induced diarrhoea while standard drug loperamide inhibited 71.25% defaecation. In magnesium sulfate-induced diarrhoea the inhibition of defaecation was 45.71 and 57.14% at the doses of 200 and 400 mg/kg respectively while loperamide inhibited 64.29% defaecation. The antidiarrhoeal effect of the extract was concentration dependent in both castor oil-induced diarrhoea and magnesium sulfate-induced diarrhoea. Phytochemical screening of the extract revealed the presence of flavonoids and alkaloids that may play key role in its antidiarrhoeal activity. The results of the present study validate the folkloric use of the rind of P. granatum in the treatment of diarrhoea. DOI: http://dx.doi.org/10.3329/icpj.v2i5.14437 International Current Pharmaceutical Journal, April 2013, 2(5): 101-104